Hubungan Pola Asuh Orang Tua dengan Perilaku Agresi pada Remaja di SMA 1 Saraswati Denpasar: Relationship Between Parenting Style and Aggressive Behavior in Adolescents in Saraswati 1 High School Denpasar - Sari, Niken Ayu Merna Eka; Andriana, Kiki Riski Fista; Mirayanti, Ni Ketut Ayu (Bali Medika Jurnal, 2021)
Adolescent aggressive behavior is an emotional state that is a mixture of feelings of frustration and hatred or anger. This is based on the emotional state in depth of each person as an important part of the emotional state that can be projected into the environment, inside or destructively. One of the factors thant influence aggressive behavior is parenting which is divided into three types, that are authoritarian parenting, permissive pareting, and democratic parenting. This research is to know relationship between the parenting style and aggression behavior of adolescent boys. The sample consisted of 129 respondents with simple random sampling technique. Data collection using a questionnaire parenting style and aggression behavior. The results showed the majority parenting style in the authoritarian parenting category was 43.4%, and the majority of the aggression behavior in the hight category was 48.1%. Based on the Spearman rank correlation test results obtained p value = 0,017 <0.05 then Ho is rejected Ha is accepted, which means there is a relationship of parenting style with aggression behavior. Conclusion there is a relationship between parenting parents with aggressive behavior inadolescent in SMA Saraswati 1 Denpasar.